boolean-algebra

Boolean algebra: (A'+B)(A+C)


I have a little problem with this expression:

x = (A'+B)(A+C)

I know it can be simplified to:

A'C+AB

since ive used some software to simplify it, but i simply can't see how it is done.

This is what i've done so far:

(A'+B)(A+C)         =>
A'A + AB + A'C + BC =>
0 + AB + A'C + BC   =>
AB + A'C + BC

I just fail to see how i can do this differently and get to the correct result.


Solution

  • So we are trying to prove:

    AB + A'C + BC = AB + A'C
    

    Using the Identity Law X = X1, the left side can become:

    AB + A'C + BC1
    

    Inverse Law 1 = X' + X

    AB + A'C + BC(A + A')
    

    Distributive Law X(Y + Z) = XY + XZ

    AB + A'C + BCA + BCA'
    

    Associative Law (XY)Z = X(YZ)

    AB + A'C + ABC + A'BC
    

    Commutative Law X + Y= Y + X

    AB + ABC + A'C + A'BC
    

    Distributive again

    AB(1 + C) + A'C(1 + B)
    

    Finally, the Null Law 1 + X = 1

    AB(1) + A'C(1)
    
    AB + A'C = AB + A'C